Duolingo-Based Vocabulary Gains in Junior High EFL Learners - Naurah Nabzifa; Niko Fediyanto (Academia Open, 2026)
General Background Vocabulary mastery is a fundamental component of English as a Foreign Language learning and supports the development of listening, speaking, reading, and writing skills, particularly in secondary education contexts. Specific Background Alongside the growth of digital learning technologies, mobile applications such as Duolingo have been increasingly integrated into English Language Teaching due to their accessibility, gamification features, and interactive learning design. Knowledge Gap Despite growing interest, empirical classroom-based evidence focusing specifically on junior high school students’ vocabulary mastery using Duolingo remains limited, especially within Indonesian EFL settings employing structured pre-test and post-test measurement. Aims This study aimed to examine whether the use of Duolingo as a digital learning medium contributes to measurable improvement in English vocabulary mastery among seventh-grade students. Results Using a quantitative pre-experimental one-group pre-test and post-test design involving 32 junior high school students, statistical analysis revealed a significant difference between pre-test and post-test scores, with a Sig. (2-tailed) value of 0.000, indicating notable vocabulary improvement after Duolingo-based instruction. Novelty The study provides focused empirical evidence on vocabulary mastery outcomes from Duolingo-supported instruction at the junior high school level within a classroom-based EFL context. Implications The findings suggest that Duolingo can serve as a supportive digital medium for vocabulary learning in secondary EFL classrooms and offer a practical reference for educators integrating mobile-assisted language learning into formal instruction. Highlights: Statistically significant score differences were observed between pre-test and post-test measurements. Learner engagement increased during gamified digital learning sessions. Mobile application use supported structured vocabulary practice in classroom instruction. Keywords: Duolingo, Vocabulary Mastery, EFL Learning, Junior High School, Mobile Assisted Language Learning